Prevalence and determinants of overweight/obesity, elevated blood pressure, and their comorbidities among primary and secondary school students in Guizhou province: a cross-sectional survey - Zhuan WANG; Xiangdong DU; Xin LI; Xiaoqin ZHANG; Xiujuan LU; Xiying PENG (Zhongguo gonggong weisheng)
ObjectiveTo analyze the prevalence and determinants of overweight/obesity and elevated blood pressure among primary and secondary school students aged 7 – 18 years in Guizhou province to provide evidence for the development of effective interventions. MethodsMeasurements of height, weight, and blood pressure and a survey of health and related factors using a questionnaire used in the National Surveillance of Common Diseases and Health-Related Factors among Students were conducted from September 2022 to March 2023 among 187 674 students aged 7 to 18 years recruited using stratified multistage cluster sampling from 2 primary schools and 2 junior high schools in each district/county and 2 senior high schools in each district and one senior high school in for all districts/counties of Guizhou province. Overweight/obesity, elevated blood pressure, and inadequate sleep were assessed according to national references including Screening for Overweight and Obesity in School-Aged Children and Adolescents: WS/T 586 – 2018, Screening Threshold for High Blood Pressure in Children and Adolescents Aged 7 – 18: WS/T 610 – 2018, and Hygiene Requirements for Daily Study Time of Primary and Secondary School Students: GB/T 17223 – 2012. Chi-square test and multivariate logistic regression analysis were used to analyze the prevalence and determinants of the two disorders and their comorbidity. ResultsAmong the 182 616 students effectively surveyed, the prevalence of overweight/obesity was 23.0%, the detection rate of elevated blood pressure was 13.9%, and the comorbidity of both conditions was 4.4%. The comorbidity rate of overweight/obesity and elevated blood pressure among students differed significantly by economic development region (4.6%, 4.3%, and 4.1% for those from undeveloped, moderately developed, and highly developed regions, respectively; χ2 = 23.679, P < 0.001), gender (4.7% for males and 4.0% for females; χ2 = 55.967, P < 0.001), and educational level (5.1% for senior high school students, 4.8% for junior high school students, and 3.9% for primary school students; χ2 = 118.414, P < 0.001). Multivariate logistic regression analysis revealed that students with the following characteristics had a significantly reduced risk of developing the comorbidity of overweight/obesity and elevated blood pressure: school boarding (odds ratio [OR] = 0.773) compared with non-boarding, 60 minutes or more of moderate-to-vigorous physical activity daily (OR = 0.773) compared with no 60 minutes of moderate-to-vigorous physical activity, spending < 1 hour or 1 – 2.9 hours per day studying after school (OR = 0.833 or OR = 0.894), and having adequate daily sleep (OR = 0.912) compared with inadequate daily sleep (P < 0.05 for all). ConclusionAmong primary and high school students in Guizhou province, the prevalence of overweight/obesity and elevated blood pressure should be of concern, especially among those in economically underdeveloped regions; males and high school students are key groups for preventing the comorbidity of overweight/obesity and elevated blood pressure; school boarding, with 60 minutes or more of moderate-to-vigorous physical activity daily and adequate daily sleep are protective factors, but spending ≥ 3 hours per day studying after school is a risk factor for the comorbidity of overweight/obesity and elevated blood pressure.